Міжнародні стандарти поліцейської діяльності у сфері захисту права власності - Єшук, О.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
In this article there are suggestions for the implementation of international normative legal acts in the sphere of protection of the right of property on the basis of their analysis in to the modern Ukrainian legislation.